Design Optimization of Stewart-Gough Platform based on Differential Evolution Algorithm - Wang Ting; Miao Hongbin; Wu Quanjun; Jin Weihe (Jixie chuandong, 2018)
The Stewart-Gough platform is optimized by using the differential evolution algorithm. Firstly,the symmetric structure and unsymmetric structure of Stewart-Gough platform are introduced. Secondly,the objective function is defined by considering the effects of the limited of workspace,the singularity con? gurations existing inside the workspace and the high cost. Finally,the tool selected for optimization is the differential evolution algorithm,and it is used to optimize the structure of Stewart-Gough platform. The results of optimization suggests that the aim of maximize the payload and minimize the forces at each leg needed to counteract external forces applied to the mobile platform can achieved by appropriate select the Stewart-Gough platform structure and parameters. Compared with other algorithms,the differential evolution algorithm has better global search ability,thus select the differential evolution algorithm as optimization tools. The optimization and simulation process are achieved by using MATLAB.